Pedographic and clinical assessment of total contact cast immobilization in diabetic foot syndrome - Sergey Valentinovich Gorokhov; Oleg Viktorovich Udovichenko; Irina Nikolaevna Ul'yanova; Evgenia Alexandrovna Berseneva; Gagik Radikovich Galstyan (Сахарный диабет)
Aim. To estimate offloading efficiency of total contact cast (TCC) and determine factors, affecting trophic ulcer response to treatment with TCC, as well as ways of their compensation. Methods. 30 patients, receiving an outpatient treatment with TCC for diabetic foot syndrome, underwent routine clinical examination, pedography and walking activity monitoring. We assessed degree of pressure reduction on the planta and the lesion area in particular, in its correlation with treatment outcome. Results. According to pedography data, TCC reduced peak pressure (maximum for all plantar zones) for 20% (from -70% to 84%) and pressure in the lesion area for 55% (-100%; +359%). Similar change was observed for "pressure-time" integral. Percentage of patients with peak pressure in ulceration area